PENERAPAN TRANSFORMASI DIGITAL MELALUI SMART LIBRARY FOR ALL (SALEA) UNTUK MEWUJUDKAN DESA LITERASI LEBAK JEPARA - Hamidaturrohmah Hamidaturrohmah; Khoirul Muslimin; Joko Minardi; Santi Andriyani; Noor Azizah (Devote: Jurnal Pengabdian Masyarakat Global, 2026)
Lebak Village is one of the leading villages in Jepara Regency; however, it still faces challenges in strengthening community functional and digital literacy. The main problems are identified in the Village Library (Perpusdes) Pondok Ilmu, including the cessation of library management for the past two years, a manual administrative system, poorly maintained reading collections, the absence of access to digital information sources, and weak collaboration among stakeholders. These conditions have limited the development of community literacy, including civic literacy, which is essential for fostering a critical, participatory, and responsible society in the digital era. This Village Partnership Community Service Program (PKDB) aims to support the realization of Lebak Village as a Literacy Village that is adaptive to digital technological developments while strengthening community civic literacy, in line with the Asta Cita agenda for human resource development and the Sustainable Development Goals (SDGs), particularly Goal 4 on quality education. The implementation methods include socialization activities, digital-based village library management training, the introduction and application of the Smart Library for All (SaLeA) application, training on the development of local digital content, multi-stakeholder mentoring, and program sustainability evaluation. The results show that the implementation of SaLeA has improved the effectiveness of village library management, digital literacy, and community participation, with a program achievement rate ranging from 95.71% to 98.57%. This program highlights the importance of digital transformation in village libraries as a sustainable strategy for fostering a literacy culture, strengthening civic literacy, and improving the quality of village human resources.